Different toxic effects of YTX in tumor K-562 and lymphoblastoid cell lines - Fernández-Araujo, Andrea; Sánchez, Jon A.; Alfonso, Amparo; Vieytes, Mercedes R.; Botana, Luis M. (Frontiers in Pharmacology, 2015)
Yessotoxin (YTX) modulates cellular phosphodiesterases (PDEs). In this regard, opposite effects had been described in the tumor model K-562 cell line and fresh human lymphocytes in terms of cell viability, cyclic adenosine 3´,5´-cyclic monophosphate (cAMP) production and protein expression after YTX treatment. Studies in depth of the pathways activated by YTX in K-562 cell line, have demonstrated the activation of two different cell death types, apoptosis and autophagy after 24 and 48 hours of treatment, respectively. Furthermore, the key role of type 4A PDE (PDE4A) in both pathways activated by YTX was demonstrated. Therefore, taking into account the differences between cellular lines and fresh cells, a study of cell death pathways activated by YTX in a non-tumor cell line with mitotic activity, was performed. The cellular model used was the lymphoblastoid cell line that represents a non-tumor model with normal apoptotic and mitotic machinery. In this context, cell viability and cell proliferation, expression of proteins involved in cell death activated by YTX and mitochondrial mass, were studied after the incubation with the toxin. Opposite to the tumor model, no cell death activation was observed in lymphoblastoid cell line in the presence of YTX. In this sense, variations in apoptosis hallmarks were not detected in the lymphoblastoid cell line after YTX incubation, whereas this type I of programmed cell death was observed in K-526 cells. On the other hand, autophagy cell death was triggered in this cellular line, while other autophagic process is suggested in lymphoblastoid cells. These YTX effects are related to PDE4A in both cellular lines. In addition, while cell death is triggered in K-526 cells after YTX treatment, in lymphoblastoid cells the toxin stops cellular proliferation. These results point to YTX as a specific toxic compound of tumor cells, since in the non-tumor lymphoblastoid cell line, no cell death hallmarks are observed.